Potato varieties for Indian subtropical plains - Sood, Salej; Bhardwaj, Vinay; Singh, R K; Luthra, S K; Kumar, Raj; Kumar, Shambhu; Gupta, V K; Chakrabarti, S K (Indian Horticulture, 2019)
The recently released new potato varieties, viz. Kufri Garima, Kufri Gaurav, Kufri Lalit and Kufri Mohan have a great potential to improve the productivity and profitability of farmers, thus improving their socio-economic conditions. All these varieties are suitable for cultivation in Indo-gangetic plains which covers >80% potato area in our country. The adoption of these varieties with an average yield increase of 10% can lead to rise of national average productivity from 22 to 25 tonne/ha.